2017
DOI: 10.1371/journal.pone.0174554
|View full text |Cite|
|
Sign up to set email alerts
|

A systematic review of rodent pest research in Afro-Malagasy small-holder farming systems: Are we asking the right questions?

Abstract: Rodent pests are especially problematic in terms of agriculture and public health since they can inflict considerable economic damage associated with their abundance, diversity, generalist feeding habits and high reproductive rates. To quantify rodent pest impacts and identify trends in rodent pest research impacting on small-holder agriculture in the Afro-Malagasy region we did a systematic review of research outputs from 1910 to 2015, by developing an a priori defined set of criteria to allow for replication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 55 publications
1
65
0
Order By: Relevance
“…First, the model could benefit from more information about M. natalensis densities in these rural villages, in order to know how many rodents need to be eliminated. Such quantitative information is available for many areas of sub-Saharan Africa, but not for the Lassa fever-endemic region [28,56]. Other important aspects that can be improved are the transmission-density relation and the percentage of chronically infected animals in the wild.…”
Section: Discussionmentioning
confidence: 99%
“…First, the model could benefit from more information about M. natalensis densities in these rural villages, in order to know how many rodents need to be eliminated. Such quantitative information is available for many areas of sub-Saharan Africa, but not for the Lassa fever-endemic region [28,56]. Other important aspects that can be improved are the transmission-density relation and the percentage of chronically infected animals in the wild.…”
Section: Discussionmentioning
confidence: 99%
“…Tanzania loses US$45 million every year in reduced maize yield (Leirs, 2003) and in some areas of South America, rodent related damage to crops can amount to up to 90% of the total annual production (Rodriguez, 1993). A recent review on the impact of pest rodents in Africa, found that losses fall between 20 and 50% (Swanepoel et al, 2017). Overall, damage to pre and post-harvest crops affects approximately 280 million undernourished people worldwide (Stenseth et al, 2003;Meerburg et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…The hoolock gibbon is a keystone mammal species in the landscape which has been studied for its distribution, population size, habitat, behavior, and conservation status [85,86]. Since rodents were viewed as a challenge to the agroecosystem, more than 162 studies have been conducted on them between 1910 and 2015 [87].…”
Section: Publications At Species Levelmentioning
confidence: 99%